Management of Project-Based Learning (PjBL) to Enhance Students’ Critical Thinking Skills in Elementary Schools - Ira Setiani; Sobari Sobari (ITScience (Information Technology and Science), 2026)
This study aims to analyze the management of the Project Based Learning (PjBL) model in enhancing students’ critical thinking skills in elementary education. The research employed a qualitative approach with a multisite case study design conducted at SDN Bunikasih 1 and SDN Vada in Cianjur Regency. Data were collected through in-depth interviews, observations, and document analysis involving school principals, teachers, and students. Data analysis was carried out using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the management of the PjBL model is implemented through four main stages: planning, organizing, actuating, and controlling. In the planning stage, teachers design project-based learning activities that integrate critical thinking indicators, although with varying levels of consistency. In the organizing stage, collaboration among teachers and the formation of heterogeneous student groups support the learning process, despite some coordination constraints. In the implementation stage, PjBL creates an active and engaging learning environment that promotes students’ participation and problem-solving skills. In the controlling stage, evaluation is conducted through supervision, reflection, and the use of critical thinking assessment rubrics, although supervision intensity is sometimes limited. The study concludes that PjBL management contributes positively to improving students’ critical thinking skills, as reflected in increased engagement, deeper understanding of learning materials, and the ability to apply knowledge in real-life contexts. However, challenges related to time management, teacher competence, collaboration, and learning facilities need to be addressed to optimize implementation.